Nano-composite fluid rolling lubricant for hot-rolled plate strip steel and preparation method of nano-composite fluid rolling lubricant

The nanocomposite fluid lubricant forms a uniform lubricating film on the surface of the roll, which solves the problems of traditional roll wear and lubricant, and achieves the long life and high-quality surface protection of the roll, which is suitable for the production needs of modern hot-rolled plate strips.

CN119144384AActive Publication Date: 2024-12-17ANGANG STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411210880.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-17
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Traditional rolls are prone to wear in the production of hot-rolled strips, resulting in surface defects and reduced service life. Traditional lubricants have problems such as harsh operating environment, easy corruption and difficult handling, resulting in early scrapping of rolls.

Method used

Using nanocomposite fluid lubricants, including graphene oxide-coated TiO2/MoS2 composite nanoparticles, surfactants, polymers, polyethers, stabilizers, antioxidants, bactericides, defoamers and pH regulators, through magnetic force Agitation and sonication form a uniform lubricating film, reducing roll wear and prolonging service life.

Benefits of technology

It achieves good protection of rolling rolls and strip surfaces, reduces friction and wear, extends the service life of rolls, and has excellent cooling, rust prevention, cleaning and safety, suitable for modern hot-rolled strip production needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020287020000051
    Figure BDA0005020287020000051
  • Figure BDA0005020287020000071
    Figure BDA0005020287020000071
Patent Text Reader

Abstract

The invention discloses a nano composite fluid hot-rolled plate strip steel rolling lubricant and a preparation method thereof, and the lubricant comprises the following components by mass: 0.2 to 3.0 wt% of graphene oxide coated TiO2 / MoS2 composite nanoparticles, 0.1 to 1.0 wt% of a surfactant, 0.1 to 3.0 wt% of a polymer, 0.5 to 2.0 wt% of polyether, 0.1 to 2.0 wt% of a stabilizer, 0.05 to 2.0 wt% of an antioxidant, 0.5 to 2.0 wt% of a bactericide, 0.25 to 1.5 wt% of an antifoaming agent, 0.5 to 5.0 wt% of a pH regulator, and the balance of water. And the balance of deionized water. According to the method, the nano composite material is added into the lubricant, a uniform lubricating film is formed in the rolling process, roller abrasion is effectively reduced, and the service life of the roller is prolonged; in addition, the lubricant also has the advantages of excellent cooling property, anti-rust property, easy cleaning property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal rolling process lubrication, and in particular relates to a nano-composite fluid hot-rolled plate and strip steel rolling lubricant and a preparation method thereof. Background Art

[0002] Hot-rolled strip is an important metal material and is widely used in modern industry. However, in the production of hot-rolled strip, due to the interaction between roller pressure and friction, the surface of the roll is easily worn, which leads to a large number of defects on the surface of the strip. Traditional methods for roller surface repair include mechanical grinding and electrospark machining, but these methods have some shortcomings, which can easily cause further damage to the surface of the roll, resulting in a reduction in the service life of the roll, thereby adversely affecting production efficiency and product quality. In addition, traditional hot-rolling oil-based lubricants have many problems during use, such as harsh operating environment, easy corruption and deterioration, and difficult sludge treatment. In addition, under the harsh environment of hot rolling with high temperature, high speed and high pressure, the surface of the roll is prone to cracking and even peeling, which leads to premature scrapping of the roll. Summary of the invention

[0003] In order to solve the above problems existing in the prior art, the present invention can form a uniform lubricating film during the rolling process by adding nanocomposite materials to the lubricant, effectively reducing the wear of the rollers and extending the service life of the rollers. The nanocomposite fluid can not only form an oxide film during the hot rolling process to play a lubricating effect, which is beneficial to improving the surface quality of the strip steel, but also the nanofluid can play a role in clean production during the hot rolling process. In addition, it also has many advantages such as excellent cooling, rust prevention, cleaning, economy and safety.

[0004] In order to achieve the above-mentioned purpose of the invention, the present invention provides a nano-composite fluid hot-rolled plate and strip rolling lubricant, which includes the following components by mass content: 0.2-3.0wt% of TiO2 / MoS2 composite nanoparticles coated with graphene oxide, 0.1-1.0wt% of surfactant, 0.1-3.0wt% of polymer, 0.5-2.0wt% of polyether, 0.1-2.0wt% of stabilizer, 0.05-2.0wt% of antioxidant, 0.5-2.0wt% of bactericide, 0.25-1.5wt% of defoamer, 0.5-5.0wt% of pH adjuster, and the balance is deionized water.

[0005] The method for preparing the above-mentioned nanocomposite fluid hot-rolled strip steel rolling lubricant comprises the following steps:

[0006] ① Adding the graphene oxide-coated TiO2 / MoS2 composite nanoparticles, surfactant, polymer, polyether, stabilizer, antioxidant, bactericide, defoamer, and pH regulator into deionized water in proportion;

[0007] ② Use a magnetic stirrer to stir and heat, heat the temperature to 75°C to 85°C, adjust the stirring speed to 1200 to 1500 rpm, and stir for 45 to 60 minutes;

[0008] ③ The suspension obtained in step ② is ultrasonically treated for 90 to 120 minutes, the ultrasonic power is set to 450 to 500 W, and finally allowed to stand at room temperature to obtain a nanocomposite fluid hot-rolled strip steel rolling lubricant.

[0009] In the above technical scheme, further, the graphene oxide-coated TiO2 / MoS2 composite nanoparticles are composed of graphene oxide, MoS2 nanoparticles and TiO2 nanoparticles; the particle size range of MoS2 nanoparticles and TiO2 nanoparticles is 30-50nm, and the composite mass ratio of graphene oxide: MoS2 nanoparticles: TiO2 nanoparticles is (1-2): (1-2): 1, and the preparation process comprises the following steps:

[0010] ① Disperse MoS2 nanoparticles in an organic solvent (conventional organic solvents such as ethanol, isopropanol, etc.), perform ultrasonic treatment for 45 to 60 minutes at an ultrasonic power of 500 to 600 W, and then add a surfactant to mix to obtain a MoS2 nanoparticle suspension.

[0011] ② Disperse TiO2 nanoparticles in an organic solvent, and use ultrasonic treatment for 45 to 60 minutes at an ultrasonic power of 500 to 600 W to obtain a TiO2 nanoparticle suspension.

[0012] ③ Drop the TiO2 nanoparticle suspension into the MoS2 nanoparticle suspension, add a surfactant, adjust the ultrasonic power to 600-800W, and heat to 80°C-85°C. The ultrasonic time is 60-90 minutes to obtain a suspension of TiO2 / MoS2 composite nanoparticles.

[0013] ④ Add graphene oxide to the suspension obtained in step ③, adjust the ultrasonic power to 800-900 W, and heat to 85° C.-90° C., and ultrasonic time for 90-120 minutes to obtain a mixed solution.

[0014] ⑤ Centrifuge the mixed solution obtained in step ④ for 30 to 45 minutes at a centrifugal speed of 12,000 to 15,000 rpm, and redisperse the obtained precipitate in ethanol to obtain a suspension.

[0015] ⑥ Filter the suspension obtained in step ⑤, and the pore size of the filter membrane is 0.2-0.5 μm.

[0016] ⑦ Centrifuge the filtered suspension again for 45 to 60 minutes, adjust the rotation speed to 18,000 to 20,000 rpm, wash and dry the obtained precipitate at 95°C to 100°C for 6 to 9 hours, and finally obtain graphene oxide-coated TiO2 / MoS2 composite nanoparticles.

[0017] Furthermore, the surfactant is composed of sodium dodecylbenzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS), and the composite mass ratio is sodium dodecylbenzene sulfonate (SDBS): sodium dodecyl sulfate (SDS) = (1-2): 1. The composite surfactant can reduce the surface tension of the liquid and increase the affinity of the nanoparticles with water, thereby reducing the interaction force between the particles and preventing the particles from aggregating with each other, which helps to evenly disperse the nanomaterial in the lubricant and maintain its stability.

[0018] Furthermore, the polymer is composed of polyvinyl alcohol (PVA) and polyacrylamide (PAM), and the compounding mass ratio is polyvinyl alcohol (PVA): polyacrylamide (PAM) = 2: (2-3). The polymer protects the metal surface in the form of a lubricating film and reduces chemical reactions such as oxidation and corrosion.

[0019] Furthermore, the polyether is composed of polyethylene glycol (PEG) and polyethylene oxide (POE), and the compounding mass ratio is polyethylene glycol:polyethylene oxide=1:1. The compounded polyether has a synergistic lubricating effect.

[0020] Furthermore, the stabilizer is polyvinyl pyrrolidone (PVP). Since the methylene carbon chain and the strongly polar acyl group in the PVP molecule have strong ability to form hydrogen bonds and complexes, they can be adsorbed on the surface of nanoparticles. This adsorption and the three-dimensional shielding effect formed by the hydrophilicity of PVP make PVP have excellent dispersion stability for nanoparticles. In the lubricant, this helps to maintain the uniform distribution of nanoparticles and prevent them from agglomerating, thereby ensuring the performance of the lubricant.

[0021] Furthermore, the antioxidant is composed of 2,6-di-tert-butyl-p-cresol (BHT) and di-tert-butyl carbonate, and the composite mass ratio is 2,6-di-tert-butyl-p-cresol (BHT): di-tert-butyl carbonate = (1-2): 1. The composite antioxidant has good stability and low volatility, and it can effectively inhibit the oxidative degradation process of the rolling lubricant, thereby extending its service life.

[0022] Furthermore, the bactericide is composed of triclosan (TCC), benzoic acid (PHB), and benzimidazole (BIT), and the composite mass ratio is triclosan:benzoic acid:benzimidazole=1:(1-2):1. The composite bactericide can inhibit the growth of microorganisms in the rolling lubricant. These microorganisms will produce acidic substances during metabolism, causing the pH value of the lubricant to decrease, thereby affecting its lubrication performance and service life. The bactericide can effectively inhibit or kill these microorganisms, thereby maintaining the stability and performance of the lubricant.

[0023] Furthermore, the defoamer is composed of polydimethylsiloxane (PDMS), defoamer SE-15, and defoamer Y-30 emulsion, and the compounding ratio is polydimethylsiloxane: defoamer SE-15: defoamer Y-30 = 2: (2 to 3): 2. The compound defoamer can help the lubricant to better form a uniform lubricating film between the roller and the plate and strip steel, thereby improving the lubrication effect and reducing friction and wear during the rolling process.

[0024] Furthermore, the pH adjuster is composed of sodium hydroxide (NaOH) and ammonium hydroxide (NH4OH), and the compound mass ratio is sodium hydroxide: ammonium hydroxide = 2: (2-3). The pH adjuster can adjust the pH of the lubricant to ensure that it is within an appropriate range, which is crucial to ensuring the stability and effectiveness of the lubricant.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a nanocomposite fluid hot-rolled plate and strip rolling lubricant and a preparation method thereof. The nanocomposite fluid lubricant has excellent lubricating properties and can provide good protection for the surfaces of rollers and strips. In addition, the lubricant also has excellent metal oxidation inhibition and rust prevention effects. The preparation method is simple and efficient, which fully meets the development needs of modern hot-rolled plate and strip steel, and also meets the needs of green and low-carbon development of the domestic steel industry. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0028] A nanocomposite fluid hot-rolled strip steel rolling lubricant, the lubricant comprising the following components by mass content: 0.2-3.0wt% of TiO2 / MoS2 composite nanoparticles coated with graphene oxide, 0.1-1.0wt% of surfactant, 0.1-3.0wt% of polymer, 0.5-2.0wt% of polyether, 0.1-2.0wt% of stabilizer, 0.05-2.0wt% of antioxidant, 0.5-2.0wt% of bactericide, 0.25-1.5wt% of defoamer, 0.5-5.0wt% of pH regulator, and the balance is deionized water.

[0029] The method for preparing the above-mentioned nanocomposite fluid hot-rolled strip steel rolling lubricant comprises the following steps:

[0030] ① Adding the graphene oxide-coated TiO2 / MoS2 composite nanoparticles, surfactant, polymer, polyether, stabilizer, antioxidant, bactericide, defoamer, and pH regulator into deionized water in proportion;

[0031] ② Use a magnetic stirrer to stir and heat, heat the temperature to 75°C to 85°C, adjust the stirring speed to 1200 to 1500 rpm, and stir for 45 to 60 minutes;

[0032] ③ The suspension obtained in step ② is ultrasonically treated for 90 to 120 minutes, the ultrasonic power is set to 450 to 500 W, and finally allowed to stand at room temperature to obtain a nanocomposite fluid hot-rolled strip steel rolling lubricant.

[0033] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.

[0034] Example

[0035] A nanocomposite fluid hot-rolled strip steel rolling lubricant, the component mass contents of the lubricants of Examples 1-10 are shown in Table 1.

[0036] Table 1 Examples 1-10 Nanocomposite fluid hot-rolled strip steel rolling lubricant components and contents / wt%

[0037]

[0038] Embodiment 1-10 The method for preparing a nanocomposite fluid hot-rolled strip steel rolling lubricant comprises the following steps:

[0039] 1. Add the graphene oxide-coated TiO2 / MoS2 composite nanoparticles, surfactant, polymer, polyether, stabilizer, antioxidant, bactericide, defoamer and pH regulator into deionized water in proportion;

[0040] The graphene oxide-coated TiO2 / MoS2 composite nanoparticles are composed of graphene oxide, MoS2 nanoparticles and TiO2 nanoparticles, the particle sizes of the MoS2 nanoparticles and the TiO2 nanoparticles are in the range of 30 to 40 nm, and the composite mass ratio of graphene oxide: MoS2 nanoparticles: TiO2 nanoparticles is 2:2:1. The preparation process thereof comprises the following steps:

[0041] ① MoS2 nanoparticles are dispersed in an organic solvent, subjected to ultrasonic treatment for 60 minutes at an ultrasonic power of 600 W, and then a surfactant is added to mix to obtain a MoS2 nanoparticle suspension.

[0042] ② Disperse TiO2 nanoparticles in an organic solvent and perform ultrasonic treatment for 60 minutes at an ultrasonic power of 600 W to obtain a TiO2 nanoparticle suspension.

[0043] ③ Drop the TiO2 nanoparticle suspension into the MoS2 nanoparticle suspension, add a surfactant, adjust the ultrasonic power to 800 W, heat to 85°C, and ultrasonic time for 90 minutes to obtain a suspension of TiO2 / MoS2 composite nanoparticles.

[0044] ④ Add graphene oxide to the suspension obtained in step ③, adjust the ultrasonic power to 900 W, heat to 90° C., and ultrasonicate for 120 minutes to obtain a mixed solution.

[0045] ⑤ Centrifuge the mixed solution obtained in step ④ for 30 to 45 minutes at a centrifugal speed of 15,000 rpm, and redisperse the obtained precipitate in ethanol to obtain a suspension.

[0046] ⑥ Filter the suspension obtained in step ⑤, and the pore size of the filter membrane is 0.2 μm.

[0047] ⑦ The filtered suspension was centrifuged again for 60 minutes, the rotation speed was adjusted to 20,000 rpm, the obtained precipitate was washed and dried at a drying temperature of 100°C and a drying time of 9 hours, and finally graphene oxide-coated TiO2 / MoS2 composite nanoparticles were obtained.

[0048] The surfactant is prepared by mixing sodium dodecylbenzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS) in a compounding mass ratio of sodium dodecylbenzene sulfonate (SDBS): sodium dodecyl sulfate (SDS) = 2:1.

[0049] The polymer consists of polyvinyl alcohol (PVA) and polyacrylamide (PAM), and is prepared by mixing polyvinyl alcohol (PVA): polyacrylamide (PAM) in a compounding mass ratio of 2:3.

[0050] The polyether is composed of polyethylene glycol (PEG) and polyethylene oxide (POE), and is prepared by mixing according to a compounding mass ratio of polyethylene glycol:polyethylene oxide=1:1.

[0051] The stabilizer is polyvinyl pyrrolidone (PVP). Since the methylene carbon chain and the strongly polar acyl group in the PVP molecule have strong ability to form hydrogen bonds and complexes, they can be adsorbed on the surface of nanoparticles. This adsorption and the three-dimensional shielding effect formed by the hydrophilicity of PVP make PVP have excellent dispersion stability for nanoparticles.

[0052] The antioxidant consists of 2,6-di-tert-butyl-p-cresol (BHT) and di-tert-butyl carbonate, and is prepared by mixing according to a compounding mass ratio of 2,6-di-tert-butyl-p-cresol (BHT): di-tert-butyl carbonate=2:1.

[0053] The bactericide consists of triclosan (TCC), benzoic acid (PHB) and benzimidazole (BIT), and is prepared by mixing triclosan:benzoic acid:benzimidazole in a compounding mass ratio of 1:2:1.

[0054] The defoamer is composed of polydimethylsiloxane (PDMS), defoamer SE-15, and defoamer Y-30 emulsion, and is prepared by mixing in a compounding ratio of polydimethylsiloxane: defoamer SE-15: defoamer Y-30=2:3:2.

[0055] The pH regulator is composed of sodium hydroxide (NaOH) and ammonium hydroxide (NH4OH), and is prepared by mixing according to a compound mass ratio of sodium hydroxide: ammonium hydroxide = 2:3.

[0056] 2. Use a magnetic stirrer to stir and heat, heat the temperature to 85°C, adjust the stirring speed to 1500 rpm, and stir for 60 minutes;

[0057] 3. The suspension obtained in step ② was ultrasonically treated for 120 minutes with the ultrasonic power set to 500 W, and finally allowed to stand at room temperature to obtain a nanocomposite fluid hot-rolled strip steel rolling lubricant.

[0058] The nanocomposite fluid hot-rolled strip rolling lubricant prepared in Examples 1-10 was tested for tribological properties using a MR-S10A four-ball friction and wear tester according to the industry standard SH / T0762-2005. Table 2 shows the implementation technical effects of the products prepared in Examples 1-10.

[0059] Table 2 Implementation technical effects of products obtained in Examples 1-10

[0060]

[0061]

[0062] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A nanocomposite fluid hot-rolled strip steel rolling lubricant, characterized in that: The lubricant comprises the following components by weight: 0.2-3.0 wt % of TiO2 / MoS2 composite nanoparticles coated with graphene oxide, 0.1-1.0 wt % of surfactant, 0.1-3.0 wt % of polymer, 0.5-2.0 wt % of polyether, 0.1-2.0 wt % of stabilizer, 0.05-2.0 wt % of antioxidant, 0.5-2.0 wt % of bactericide, 0.25-1.5 wt % of defoamer, 0.5-5.0 wt % of pH regulator, and the balance is deionized water; The method for preparing the above-mentioned nanocomposite fluid hot-rolled strip steel rolling lubricant comprises the following steps: ① Adding the graphene oxide-coated TiO2 / MoS2 composite nanoparticles, surfactant, polymer, polyether, stabilizer, antioxidant, bactericide, defoamer, and pH regulator into deionized water in proportion; ② Use a magnetic stirrer to stir and heat, heat the temperature to 75°C to 85°C, adjust the stirring speed to 1200 to 1500 rpm, and stir for 45 to 60 minutes; ③ The suspension obtained in step ② is ultrasonically treated for 90 to 120 minutes, the ultrasonic power is set to 450 to 500 W, and finally allowed to stand at room temperature to obtain a nanocomposite fluid hot-rolled strip steel rolling lubricant.

2. The rolling lubricant according to claim 1, characterized in that The graphene oxide-coated TiO2 / MoS2 composite nanoparticles are composed of graphene oxide, MoS2 nanoparticles, and TiO2 nanoparticles, and the composite mass ratio of graphene oxide: MoS2 nanoparticles: TiO2 nanoparticles is (1-2): (1-2):

1. The preparation process thereof comprises the following steps: ① Disperse MoS2 nanoparticles in an organic solvent, perform ultrasonic treatment for 45 to 60 minutes at an ultrasonic power of 500 to 600 W, and then add a surfactant to mix to obtain a MoS2 nanoparticle suspension; ② Dispersing TiO2 nanoparticles in an organic solvent, and subjecting the mixture to ultrasonic treatment for 45 to 60 minutes at an ultrasonic power of 500 to 600 W to obtain a TiO2 nanoparticle suspension; ③ Dropping the TiO2 nanoparticle suspension into the MoS2 nanoparticle suspension, adding a surfactant, adjusting the ultrasonic power to 600-800W, and heating to 80°C-85°C, the ultrasonic time is 60-90 minutes, and obtaining a suspension of TiO2 / MoS2 composite nanoparticles; ④ Add graphene oxide to the suspension obtained in step ③, adjust the ultrasonic power to 800-900W, and heat to 85°C-90°C, and the ultrasonic time is 90-120 minutes to obtain a mixed solution; ⑤ Centrifuge the mixed solution obtained in step ④ for 30 to 45 minutes at a centrifugal speed of 12,000 to 15,000 rpm, and redisperse the obtained precipitate in ethanol to obtain a suspension; ⑥ Filter the suspension obtained in step ⑤, wherein the pore size of the filter membrane is 0.2 to 0.5 μm; ⑦ Centrifuge the filtered suspension again for 45 to 60 minutes, adjust the rotation speed to 18,000 to 20,000 rpm, wash and dry the obtained precipitate at 95°C to 100°C for 6 to 9 hours, and finally obtain graphene oxide-coated TiO2 / MoS2 composite nanoparticles.

3. The rolling lubricant according to claim 1, characterized in that The surfactant is composed of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate, and the compounding mass ratio is sodium dodecylbenzene sulfonate: sodium dodecyl sulfate = (1-2): 1; the polymer is composed of polyvinyl alcohol and polyacrylamide, and the compounding mass ratio is polyvinyl alcohol: polyacrylamide = 2: (2-3).

4. The rolling lubricant according to claim 1, characterized in that The polyether is composed of polyethylene glycol and polyethylene oxide, and the compounding mass ratio is polyethylene glycol:polyethylene oxide=1:1; The stabilizer is polyvinyl pyrrolidone.

5. The rolling lubricant according to claim 1, characterized in that The antioxidant consists of 2,6-di-tert-butyl-p-cresol and di-tert-butyl carbonate, and the composite mass ratio is 2,6-di-tert-butyl-p-cresol (BHT): di-tert-butyl carbonate = (1-2): 1; the fungicide consists of triclosan, benzoic acid, and benzimidazole, and the composite mass ratio is triclosan: benzoic acid: benzimidazole = 1: (1-2):

1.

6. The rolling lubricant according to claim 1, characterized in that The defoamer is composed of polydimethylsiloxane, defoamer SE-15, and defoamer Y-30, and the compounding ratio is polydimethylsiloxane: defoamer SE-15: defoamer Y-30=2:(2-3):2; the pH regulator is composed of sodium hydroxide and ammonium hydroxide, and the compounding mass ratio is sodium hydroxide: ammonium hydroxide=2:(2-3).

Citation Information

Patent Citations

  • Hot rolling oil for steel member and method for hot rolling steel member

    CN101605878A

  • Rolling-use water base nano lubricant based on graphene oxide (GO) and preparation method thereof

    CN106566647A

  • Fullerene-carbon nanotube-graphene oxide lubricating additive and preparation thereof

    CN107011966A

  • High-dispersity nano molybdenum disulfide water-based rolling liquid and preparation method thereof

    CN112940836A

  • Titanium alloy water-based rolling liquid and preparation method thereof

    CN114874833A